Systematic Review and Meta-Analysis: Prevalence of Small Intestinal Bacterial Overgrowth in Chronic Liver Disease - Shah, Ayesha; Shanahan, Erin; Macdonald, Graeme A.; Fletcher, Linda; Ghasemi, Pegah; Morrison, Mark; Jones, Mike; Holtmann, Gerald (Seminars in Liver Disease, 2017)
The authors conducted a meta-analysis of the prevalence of small intestinal bacterial overgrowth (SIBO) in patients with chronic liver disease (CLD) and controls. Using the search terms “small intestinal bacterial overgrowth (SIBO)” and “chronic liver disease (CLD)” or “cirrhosis,” 19 case-control studies were identified. Utilizing breath tests, the prevalence of SIBO in CLD was 35.80% (95% CI, 32.60–39.10) compared with 8.0% (95% CI, 5.70–11.00) in controls. Using culture techniques, the prevalence was 68.31% (95% CI, 59.62–76.00) in CLD patients as compared with 7.94% (95% CI, 3.44–12.73) in controls. No difference between cirrhotic and noncirrhotic patients was found. SIBO is significantly more frequent in CLD patients as compared with controls. The association of SIBO and CLD was not confined to patients with advanced CLD, suggesting that SIBO is not a consequence of advanced liver disease but may play a role in the progression of CLD.
Keywords: cirrhosis; bacterial overgrowth; prevalence; breath tests; NAFLD